PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Survei pada Konsumen Lumbung Batik Surakarta) - Sunarso, Devik Fatmawati, Rahayu Triastity & (Universitas Slamet Riyadi, 2017)
Lumbung Batik Surakarta is a clothing store that sells a wide range of fashion formen and women, both for children and adults with its main raw material is the motif.Surakarta Batik barn in an effort to boost consumer purchasing decisions trying tomaintain product quality, maintain brand image and foster consumer confidence. Thepurpose of this study was to analyze the significance of the influence of product qualityand brand image of the trust. Analyze the significance of the influence of product quality,brand image and trust on consumer purchasing decisions. Analyze the significance of theinfluence of product quality and brand image on purchasing decisions with confidenceas an intervening variable. This study used survey methods, the type of data usedquantitative and qualitative data, the data source used primary data and secondary data.The population in this study is consumers who shop at Lumbung Batik Surakarta in theperiod January 2017 - February 2017. The number of samples in this study as many as100 people, the sampling technique uses accidental sampling. Data collection methodsare used: questionnaires and documentation. Data analysis technique used to test thevalidity, reliability test, classic assumption test, and path analysis. In conclusion: Theproduct quality and brand image significant effect on confidence. Product quality, brandimage and confidence have a significant effect on consumer purchasing decisions.Product quality and brand image significantly influence purchase decisions withconfidence as an intervening variable.Keywords: product quality, brand image, confidence, purchasing decisions.